The Stereotypical Women and Empowered Women Narration in the Novel Bidadari Bermata Bening - Dian Rizky Azhari; M. Yoesoef; Turita Indah Setyani (Future Science, 2022)
A cursory reading of the novel Bidadari Bermata Bening will give the impression that this novel voices the idea of empowered women. However, it turns out that there is also a strong narrative of stereotypical women in the text. Based on the explanation, this study aims to reveal why there are two such contradictory narratives in one text. This study uses an analysis of the narrative elements of the text based on Gerard Genette's theory, assisted by the theory of the power of discourse from Michel Foucault. The text is explored intrinsically, through analysis of characterizations, narrator's voice, and character’s focalization. Then by using discourse analysis, the text is analyzed to find out which discourses play in it and build ideological ideas. Based on the results of the analysis, it appears that the narrative of empowered women emerges through an omniscient narrator and is assisted by voices (focalization) from subordinate characters. Meanwhile, the narrative of stereotypical women emerges from the subjectivity of the women main character. Behind the contradictions of the two narratives, it appears that the discourse of Islamic values actually dominates the construction of ideas, both narratives of empowered women and stereotypical women. The text legitimizes both narratives by using religious arguments, in this case Islam. This can be interpreted as a text effort in propagating the discourse of Islamic women.